Integrated System Design for Library and Information Systems - Neelameghan, A. (Journal of Information and Knowledge, 1986)
Information is an essential input in coordination of all human activities. Coordinated information system saves time and effort of individuals and groups, A system design for integrated information system based on a detailed Matrix of Data Elements is presented. Three different experiment models are tested in negotiating the data bases.